Enunciative prospecting: the semiotic start of Louis Marin - Fabbri, Paolo (E|C, 2020)
Louis Marin's work on enunciation was seminal. Here I am interested in taking it up and updating it. The theory of enunciation has not yet exhausted its possibility. On the one hand we should deepen its heuristic value, on the other we should try a delimitation.